Fisheries management for food security in the Maldives - Nadhiya Abdulla; Natalia Vasylieva; Iryna Volovyk (Agricultural and Resource Economics)
Purpose. The goal of the study was to assess trends in providing food security with a special emphasis on efficiency of the local fisheries and offer evidence-based improvements, which can improve resource management and protect disadvantaged population in the Maldives from nutrition insecurity aggravated by strong import dependency.